The Implementation Of Inquiry-Based Learning In Teaching Reading At The First Year Of SMP Muhammadiyah 4 Surakarta - Fadlilah, Oktafiningrum Umi, Aryati Prasetyarini, M.Pd, Siti Fatimah, S. Pd, M. Hum (2015)
This research aims at describing the implementation of inquiry-based learning in teaching reading and the problems faced by the teacher in implementing the method at the first year of SMP Muhammadiyah 4 Surakarta. The writer gets the data of this research from event, informant and document. The methods of collecting data are observation, interview, and documentation. This research uses descriptive qualitative where is the process of simplification of data to make easier to read. The methods for analysis data are data reduction, data display, also conclusion and verification. The result of the analysis shows that: 1) the implementation of inquiry-based learning in teaching reading at the first year of SMP Muhammadiyah 4 Surakarta consists of three stage namely, exploration, elaboration and confirmation. The implementation of method is less complete because the activities in standard process are not implemented in teaching reading process fully. 2) the problem faced by the teacher implementing the method are lack of knowledge about inquiry-based learning and how to implement the method, class management, limited time, lack of material and lack of teaching media. The solutions for the problems are: a) the headmaster should give evaluation to the teacher in using method and media in teaching learning process and give chance for the teacher to follow the Seminar, teacher training and Diklat. b) The teacher should have knowledge before they implement this method in the class, so in the teaching learning process there will not be misunderstanding.